Synthesis and Assessment of Antioxidant Capacity of Hypoglycaemic Plants: Exploring the Potential of Hypoglycaemic Plants in Antioxidant Capacity and Diabetes Treatment (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Natural products are critical to health-care systems. The numerous sources of herbalsubstances and plants have served as the foundation for chemical compounds utilised as inputmaterials in pharmaceutical formulations such as synthetic medications. Multiple approaches wereemployed to assess the antioxidant activity of the selected plant extracts. The goal of this research is toassess the characteristics and treatment of diabetes patients in our country. The study emphasises thenecessity and attention on medicinal herbal plants in order to separate the bioactive components andmake their hypoglycaemic effects evident. Diabetes was treated with a drug made from medicinal herbs.The biological effects of these chemicals are discovered, which facilitates in the conversion of thesesubstances into medications or lead molecules for further drug development. As a result, the goal was tocharacterise the active components recovered from the strong extract using chromatography. It providesthe community with effective, cheap therapy while increasing public trust in alternative medicines.